Modelling of behaviour of metals at high strain rates - Panov, Vili (Cranfield University, 2006)
The aim of the work presented in this thesis was to produce the improvement of the existing simulation tools used for the analysis of materials and structures, which are dynamically loaded and subjected to the different levels of temperatures and strain rates. The main objective of this work was development of tools for modelling of strain rate and temperature dependant behaviour of aluminium alloys, typical for aerospace structures with pronounced orthotropic properties, and their implementation in computer codes. Explicit finite element code DYNA3D has been chosen as numerical test-bed for implementation of new material models. Constitutive model with an orthotropic yield criterion, damage growth and failure mechanism has been developed and implemented into DYNA3D. Second important aspect of this work was development of relatively simple experimental methods for characterization of engineering materials, and extensive experimental work has been undertaken. Tensile test has been used for the characterisation of two aluminium alloys, at different levels of the strain rates and temperatures, and for three different orientations of materials. The results from these tests allowed derivation of material constants for constitutive models and lead to a better understanding of aluminium alloy behaviour. Procedures for derivation of parameters for temperature and strain rate dependant strength models were developed and parameters for constitutive relations were derived on the basis of uniaxial tensile tests. Taylor cylinder impact test was used as a validation experiment. This test was used to validate the implementation, and accuracy of material model in computer code. At the end of each incremental development, validation of the constitutive material model has been performed through numerical simulations of Taylor cylinder impact test, where simulation results have been compared with the experimental post-test geometries in terms of major and minor side profiles and impact-interface footprints. Plate impact test has been used to determine the material properties at high strain rate, and to investigate damage evolution in impact-loaded material. Initially the material model has been designed as a temperature and strain rate dependant strength model in a simple isotopic form, which then has been tested and verified against the experimental results. Coupling of the Hill’s orthotropic yield criterion with isotropic, temperature and strain rate dependant, hardening material model, has been chosen to suit the orthotropic behaviour. Method for calibration of orthotropic yield criterion has been developed and parameters have been identified for the orthotropic model under the associated flow rule assumption and in case of plane stress on the basis of tensile and cylinder impact tests. The complexity of the model has been further increased through coupling of hardening model with orthotropic yield criterion including damage evolution and failure criteria. The constitutive model was developed within the general framework of continuum thermodynamics for irreversible processes, and plate impact test and tensile tests have been used for determination of parameters for damage part of the new material model.